APLIKASI PENGUKURAN KEPUASAN BEKERJA DARI RUMAH PADA DOSEN UNIVERSITAS ANDALAS BERDASARKAN SIKAP QANA’AH MENGHADAPI COVID-19 - Tri Rahayuningsih; Anip Febtriko; Guslendra Guslendra; Rini Sovia; Refli Noviardi (LPPM Universitas Abdurrab, 2022)
The policy of the Covid-19 Pandemic that requires working from home during the quarantine period has an impact on the productivity of lecturers because work satisfaction is disrupted due to the dual roles performed by lecturers at home. Psychological problems such as boredom, fatigue, and stress that arise during this physical distancing period require an attitude to be able to accept unpleasant situations without excessive panic, namely Qana'ah (contentment) as a psychological model that is deemed appropriate to be a factor in job satisfaction from home to Andalas University (Unand) lecturers during the Covid-19 pandemic. Research on qana'ah in work is associated with performance and employee motivation. Thus, job satisfaction is about someone who loves his job, and finds accomplishment and fulfillment in it. It is also a mixture of a person's feelings and emotions about how work affects his life, including in the working from home period like today. The purpose of this study was to determine the relationship between qana'ah attitudes and job satisfaction from home at Unand lecturers during the Covid-19 pandemic. The planned activities that have been carried out are using a mix method, first a qualitative research method to formulate a measurement construct through open interviews with several religious leaders and Unand lecturers. Second, the quantitative stage for the trial was carried out through an online questionnaire for Unand lecturers. Third, after getting a valid item, a measuring instrument in the form of a scale is compiled and distributed online again. Fourth, making measurement applications on websites based on expert systems, so as to produce job satisfaction measurement products that can be used anytime.